2023
DOI: 10.1111/jcmm.17735
|View full text |Cite
|
Sign up to set email alerts
|

NDUFV1 attenuates renal ischemia–reperfusion injury by improving mitochondrial homeostasis

Abstract: Acute kidney injury (AKI) is a disease with high mortality and morbidity. 1 The causes of AKI are various, among them, septicemia, low perfusion, and nephrotoxic injury are the most common risk factors. 2 Low perfusion injury is a hallmark of AKI, which is also a main leading cause for chronic kidney disease (CKD). 3,4 The severity, duration, frequency, and age determine whether AKI develops into CKD. 5 Many events have been shown to be involved in the pathogenesis of AKI, such as inflammatory response, renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…One of these, NDUFV1, was recently shown to be, by itself, sufficient to provide protection against IRI. 50 Interrogating the mechanisms by which DC 8 protected the complex I was beyond the scope of this study. However, we speculate that it may be due to decreased oxidative stress.…”
Section: Discussionmentioning
confidence: 98%
“…One of these, NDUFV1, was recently shown to be, by itself, sufficient to provide protection against IRI. 50 Interrogating the mechanisms by which DC 8 protected the complex I was beyond the scope of this study. However, we speculate that it may be due to decreased oxidative stress.…”
Section: Discussionmentioning
confidence: 98%
“…NADH: Ubiquinone Oxidoreductase Core Subunit V1 (NDUFV1) is a nuclear-encoded structural subunit of CI and its mutations are associated with Leigh syndrome (LS), diffuse leukoencephalopathy, and Parkinson’s disease ( 48 , 49 ). According to previous research, the reinforcement expression of NDUFV1 has turned out to reduce serum creatinine and blood urea nitrogen, attenuate proximal tubule damage, and repress cell apoptosis in renal ischemia/reperfusion (I/R) mice, which may be due to the improved mitochondrial metabolism, and reduced oxidative stress by overexpressed NDUFV1 ( 50 , 51 ). Having shown that the expression level of NDUFV1 was decreased in LN in our study and the classical pathway analysis of IPA indicated that NDUFV1 was related to ‘oxidative phosphorylation’ and ‘mitochondrial dysfunction’, we thus speculate that NDUFV1 deficiency could impair mitochondrial metabolism and homeostasis in renal tissue, contributing to the progress of LN.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, it is not hard to notice that new agents modulating oxidative stress and mitochondrial metabolism might have a potent therapeutic role in the treatment of LN; Complex I (CI, NADH: ubiquinone oxidoreductase) refers to mitochondrial oxidative phosphorylation (OxPhos) enzyme complex consisting of 45 subunits, and its dysfunction would generally impair energy production and affect various organs including kidneys (47). NADH: Ubiquinone Oxidoreductase Core Subunit V1 (NDUFV1) is a nuclear-encoded structural subunit of CI and its mutations are associated with Leigh syndrome (LS), diffuse leukoencephalopathy, and Parkinson's disease (48,49). According to previous research, the reinforcement expression of NDUFV1 has turned out to reduce serum creatinine and blood urea nitrogen, attenuate proximal tubule damage, and repress cell apoptosis in renal ischemia/ reperfusion (I/R) mice, which may be due to the improved mitochondrial metabolism, and reduced oxidative stress by overexpressed NDUFV1 (50, 51).…”
Section: Discussionmentioning
confidence: 99%
“…Approaches such as mitochondrial gene delivery [ 52 ], coenzyme Q 10 administration [ 53 ], and mitochondrial transplantation [ 54 , 55 ] have been shown to be able to attenuate kidney injury. Supporting these findings, the overexpression of reduced nicotinamide adenine dinucleotide (NADH):ubiquinone oxidoreductase core subunit V1 (NDUFV1), which encodes a 51-kDa subunit of complex I, can attenuate kidney IR injury by improving mitochondrial function [ 56 ].…”
Section: Therapeutic Strategies Of Kidney Ischemia-reperfusion Injury...mentioning
confidence: 99%